Efeitos isolados e combinados dos inseticidas fipronil e tiametoxam para a abelha brasileira Melipona scutellaris Latreille, 1811 (Hymenoptera, Apidae) - Araújo, Jéssica Freitas (2017)
Pollinators are responsible for tropical forests polinization and also have direct and indirect action on human feeding. The pollinators are majorly represented by bees. Even though, this contribution has been affected by numerous factors, among them, agrochemicals. The tiametoxam and fipronil insecticides, from neonicotinoides and fenilpirazois classes, respectively, present numerous negative effects, including biochemical alterations, in different bees species. Therefore, the aim of this paper was to analyze, through biochemical techniques, acetilcolinesterase (AChE) and carboxilesterase (CaE) enzyme activities in the head and glutationa S-transferase in the intestines of Melipona scutellaris worker bees, exposed to the mentioned insecticides, combined and isolated. Bees forage were collected and divided into four experimental groups: Control, acetone control, LC50/2 (0,0226 ng i.a. tiametoxam/μL and 0,0056 ng i.a. fipronil/μL) and LC50/5 (0,00906 ng i.a. tiametoxam/μL e 0,0022 ng i.a. fipronil/μL) orally exposed, combined and isolated, for 1, 6, 12, 24, 48 and 96 hours. The brain and the intestines were dissected, weighted and submitted to LS drainage buffer solution, macerated and centrifuged. The absorbance readings were done in 412, 410, and 340 nm wavelength, respectively. The data was analyzed by the Mann – Whitney e Kruskal – Wallis tests. The results showed alterations in the AChE tissue activity to the fipronil insecticide raising in 1 hour (LC50/2 and LC50/5) and decreasing in 6 hours (LC50/2 and LC50/5) and 12 hours (LC50/2) and raising again in 96 hours (LC50/2 and LC50/5). To the tiametoxam insecticide there was a decrease at 6 hours (LC50/2 and LC50/5), 12 hours (LC50/2) and 24 hours (LC50/5) and a raise at 96 hours (LC50/2 and LC50/5). Combining these insecticides it was observed a decrease in AChE LC50/2 activity (6 and 12 hours) and LC50/5 (6 and 24 hours) and a raise in LC50/2 and LC50/5 (96 hours). In specific activity there was a decrease at 6 hours (Fipronil LC50/2 and LC50/5 and Combined LC50/2), 48 hours (Tiametoxam LC50/5) and 96 hours (Fipronil LC50/2 and Combined LC50/5). The following patterns were detected for the detoxification enzyme tissue CaE-3: Fipronil insecticide – decrease in 12 hours (LC50/2) and raise in 96 hours (LC50/2) and combined – activity decrease in CL50/5 group (6 hours). Differences statistically relevant weren’t identified in groups exposed exclusively to tiametoxam insecticide. Considering the GST activity, the acetone group obtained raise in one hour exposure; groups exposed to the fipronil insecticide LC50/5 (1 hour), LC50/2 and LC50/5 (96 hours) obtained decrease and raise in this enzyme activity, respectively. Considering tiametoxam insecticide it was observed a raise in the activity at 6 hours (LC50/2 and LC50/5) and at 12 hours (LC50/5); there was increase in the combination for the groups: LC50/2 (48 and 96 hours) and LC50/5 (6 and 12 hours). This way, we can conclude that the insecticides, combined or isolated, affect the analyzed enzymes, reflecting in the toxicity of these individuals when exposed to sublethal doses; they may cause death of the individuals, hives destructure, and impact ecosystem directly.